Factors affecting the Yen dollar exchange rate - Soo, Woan Shy (2014)
After the breakdown of the Bretton Woods in 1971, the Yen exchange rate was allowed to float freely. For the past two decades, the Yen has appreciated significantly accompanied by increasing current account surplus in Japan. In this study, the Yen-Dollar bilateral rate is examined using a synthesised model that is based on the Flexible Price Monetary approach to exchange rate determination, but with wealth included.